Avoiding the Pitfalls in Taxing Financial Intermediation - Honohan, Patrick (World Bank, Washington, DC, 2014)
Enthusiasts for financial sector tax reform typically come either with some form of "flat tax" (including value added tax on financial services, zero taxation on capital income, or a universal transactions tax) or advocating corrective taxes designed to offset market failures or achieve other targeted objectives. As a result the tax systems in most countries often end up with a complex mixture. Honohan argues that practical policy for taxation of the financial sector needs to take into account two key features of the sector: its capacity for arbitrage and its sensitivity to inflation and thus to nonindexed taxes. Where these aspects have been neglected, poorly constructed tax systems-whether the consequence of a drive for revenue or of misdirected sophistication-often have sizable unexpected side effects. A defensive stance making the minimization of such distortions as its cornerstone is the best policy.